Игрушки и игры как элемент социализации детей северной части Буковины в X-XIV вв. - Возний, Ігор (Stratum plus. Археология и культурная антропология, 2023)
I. P. Vozny Toys and Games as an Element of Children’s Socialization in Northern Part of Bukovina in 10th—14th Centuries The article considers one of the important elements of the child’s world and discovery process through the games and the toys. These toys and games play an important role during child’s life and are an important element and the way of education and upbringing. Nevertheless, the researchers have paid little attention to this category of artifacts, hardly referring to them in their publications. Clay zoomorphic and anthropomorphic toys took an important place in the culture of the ancient population. In the researched area, explorers have found a clay figurine of an animal and a clay horseman figurine which are the examples of the graphic toy type. Clay Easter eggs (pysanka) and bone whistles belong to the rattling toys. The children’s tableware and «coins» belonged to the category of household items. Various games also played an important role in the upbringing of children and their daily life. For researchers, they are of special interest, since they were not meant just to entertain children, but had a symbolic and magical meaning. Archaeological materials are of great importance due to the small number of extant written sources. The artifacts that were found in the explored area indicate the existence of the chess game. There is also evidence of using the astragalus and dice in the games. We have more opportunities to learn about the life and culture of the local inhabitants of the medieval period in the northern part of Bukovina by studying children’s toys and play accessories.
Keywords: toys,; games,; astragalus,; dice,; chess,; toy horseman; pysanka,; children’s tableware; whistles